Professional Practice and Neurosurgery: What Every Neurosurgeon Should Know about Malpractice - Becerra Romero, Alicia Del Carmen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction The objective of the present study was to review the epidemiological aspects of malpractice in neurosurgery and to identify preventive measures regarding malpractice for neurosurgeons.Methods The following terms (alone or in combination) were searched in the PubMed and Biblioteca Virtual em Saúde databases: neurosurgery (neurocirurgia), lawsuits (ações judiciais), malpractice (erro médico), and litigation (litígio) and identifying studies on these topics published from 2000 to April 2018.Literature Review In Brazil, 6.9% of the physicians are sued per year. The most common type of malpractice alleged in litigation is negligence. According to the literature, the neurosurgical disease that has sparked the most litigation is spinal disease. The outcomes of these cases vary: sometimes the neurosurgeon prevails, and at other times the plaintiff prevails. To prevent or reduce malpractice claims, the neurosurgeon should take the following precautions: 1. follow medical protocols; 2. perform surgeries in an environment consistent with good medical practice; 3. evaluate and monitor antibiotic prophylaxis; 4. develop a good relationship with the patient based on ethics, good faith and transparency; 5. request the presence of the patient and of his or her family when there is a problem in order to didactically explain the case; 6. keep good medical records to document all of the actions performed (informed consent and description of the surgery and of the pre and postoperative); 7. always seek technical improvement (continuing education/professional development); 8. in the case of attending physicians, monitor patients, treating any postoperative complications; and 9. conduct multidisciplinary team meetings to optimize treatment decisions and to share responsibility for making difficult decisions.
Keywords: neurosurgery; lawsuits; malpractice; litigation